Zirconia composite sintered body, and method of producing the same

JP2025028914APending Publication Date: 2025-03-05KURARAY NORITAKE DENTAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024202876
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2024-11-21
Publication Date
2025-03-05

AI Technical Summary

Benefits of technology

【0020】 本発明によれば、歯科用として好適な強度と透光性を有し、かつ機械加工性に優れる、ジルコニア複合焼結体を提供できる。 また、本発明によれば、焼結体の状態で機械加工することができ、機械加工による加工時間が短く、かつ、加工用工具の消耗を抑制でき、1つの加工用工具を用いた連続的な加工(以下、単に「連続加工」とも称する)によって削り出すことができる歯科用補綴物の個数が多く、生産性及び経済性に優れるジルコニア複合焼結体を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025028914000001
    Figure 2025028914000001
  • Figure 2025028914000002
    Figure 2025028914000002
  • Figure 2025028914000003
    Figure 2025028914000003
Patent Text Reader

Abstract

To provide a zirconia composite sintered body having strength and light transmissivity suitable for dentistry and having excellent machinability.SOLUTION: A zirconia composite sintered body according to the present invention includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transition of zirconia, and Nb2O5 and / or Ta2O5, in which the total content of ZrO2 and HfO2 is 78 to 97.5 mol% in 100 mol% of the total of ZrO2, HfO2, the stabilizer, Nb2O5 and Ta2O5, the content of the stabilizer is 1 to 12 mol%, the total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, and a group I element and TiO2 are further included.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a zirconia composite sintered body and a method for producing the same, and more particularly to a zirconia composite sintered body which is excellent in strength and translucency and also in processability in a sintered state, and a method for producing the same. [Background technology]

[0002] Ceramics made of metal oxides have been widely used industrially, and zirconia sintered bodies are particularly used as dental materials for dental prostheses due to their high strength and aesthetic properties.

[0003] Zirconia sintered bodies have excellent strength, so when they are used as dental materials such as prostheses, problems such as breakage rarely occur. In addition, zirconia sintered bodies have high translucency and are less likely to be discolored in the oral cavity, so they are also excellent in aesthetics. On the other hand, after being made into a completely sintered sintered body, they have high hardness and are almost impossible to process with dental processing machines. For example, if a zirconia sintered body having a cubic shape is machined to obtain a zirconia sintered body having a shape that matches the shape of a patient's teeth, the consumption of metal processing tools will be very large, and it will take a huge amount of time to manufacture even just one dental prosthesis.

[0004] For these reasons, when using a zirconia sintered body for dental material applications, it is usually not a completely sintered sintered body, but a calcined body in a semi-sintered state that is easy to process is processed into the shape of a desired dental prosthesis, and then further sintered to produce a sintered body processed into the shape of the intended dental prosthesis. After that, the sintered body is subjected to slight adjustment processing so that the sintered body having the shape of the dental prosthesis fits comfortably when it is worn in the oral cavity of a patient at a dental clinic. Moreover, in recent years, when the calcined body is processed into the desired shape of a dental prosthesis, machining using a CAD / CAM system is used to obtain a shape that matches the patient's tooth in the treatment area, and calcined bodies (mill blanks) for CAD / CAM systems are widely used.

[0005] As described above, when using zirconia sintered bodies for dental material applications, major machining is avoided after sintering due to the specific problems in sintering zirconia, and processing of the sintered body is limited to minor adjustments when it is fitted in the oral cavity of a patient at a dental clinic. In other words, measures are taken in dental material applications that correspond to the gradual changes in physical properties caused by sintering zirconia.

[0006] In addition, in dental treatment, taking into consideration the unique circumstances resulting from the physical properties of the above-mentioned zirconia sintered body, treatment is generally carried out through many steps, including a step of acquiring information on the shape of the patient's oral cavity, such as information on the dentition, a step of machining a calcined body (mill blank) into the shape of the desired dental prosthesis using a CAD / CAM system based on the acquired information, a step of sintering the calcined body having the shape of the desired dental prosthesis to obtain a sintered body, and a step of making slight adjustments to the sintered body so that it fits comfortably in the patient's oral cavity when worn at a dental clinic.

[0007] As described above, in dental treatment using a dental prosthesis made of zirconia sintered body, it is difficult to complete all the above steps in one visit to the dental clinic. Therefore, even for treatment of one tooth, multiple visits to the dental clinic are required, and the treatment period from start to finish often takes more than one month.

[0008] On the other hand, from the patient's perspective, it is desirable to minimize the number of visits to the hospital in order to reduce the time it takes for new artificial teeth to be fitted after treatment and to reduce the burden of having to go to the hospital, and the need to complete treatment in a short period of time is increasing year by year.

[0009] If it were possible to perform significant machining on the zirconia sintered body, it would eliminate the need to machine the calcined body first and then produce a sintered body by sintering. After obtaining information on the shape of the patient's mouth, the unmachined sintered body could be machined into the shape of the desired dental prosthesis using a CAD / CAM system based on that information, and the prosthesis could then be fitted into the patient's mouth and fine-tuned, allowing dental treatment to be completed in one day.

[0010] In addition, when using dental prostheses, dental treatment that can be completed in one day is possible when materials other than zirconia, such as lithium disilicate glass ceramics and feldspar-based glass ceramics, are used. However, in the case of zirconia sintered bodies, there are unique circumstances resulting from the physical properties of the zirconia sintered bodies, making it very difficult to realize this.

[0011] As described above, zirconia is in high demand in terms of strength and aesthetics, and in response to the increasing need to shorten treatment periods, zirconia sintered bodies have been proposed that have excellent machinability in the sintered state and can be processed from a prismatic or disc-shaped mill blank into the shape of a desired dental prosthesis (e.g., Patent Documents 1 and 2).

[0012] For example, Patent Document 1 discloses a processable zirconia that is a sintered body formed so as to contain a tetragonal zirconia composite powder containing 79.8 to 92 mol% ZrO2, 4.5 to 10.2 mol% Y2O3, 3.5 to 7.5 mol% Nb2O5 or 5.5 to 10.0 mol% Ta2O5, and a TiO2 nanopowder whose mass ratio to the zirconia composite powder is more than 0 mass% and 2.5 mass% or less, and a method for producing the same.

[0013] Patent Document 2 discloses a machinable zirconia composition using a raw material containing 78 to 95 mol% ZrO2, 2.5 to 10 mol% Y2O3, 2 to 8 mol% Nb2O5, and / or 3 to 10 mol% Ta2O5, in which the main crystal phase of ZrO2 is monoclinic, and a method for producing the same. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] JP 2015-127294 A [Patent Document 2] International Publication No. 2021 / 132644 Summary of the Invention [Problem to be solved by the invention]

[0015] The zirconia sintered bodies disclosed in Patent Documents 1 and 2 can be machined even in a sintered state. However, the processing time required to cut out a dental prosthesis is long, and there is room for improvement in terms of shortening treatment time. In addition, although the zirconia sintered bodies disclosed in Patent Documents 1 and 2 can be machined, the number of dental prostheses that can be obtained by continuous machining using one machining tool is small, and the machining tool wears out quickly, so that the machining tool needs to be replaced more frequently, the tool replacement time increases, and productivity and cost efficiency decrease.

[0016] Furthermore, if the hardness of the material is reduced in order to improve machinability, there is a problem in that the strength of the material is reduced.

[0017] An object of the present invention is to provide a zirconia composite sintered body having strength and translucency suitable for dental use and excellent machinability. [Means for solving the problem]

[0018] As a result of intensive research into solving the above problems, the inventors have found that the problems can be solved by further containing a Group I element and TiO2 in a zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of suppressing the phase transition of zirconia, and Nb2O5 and / or Ta2O5 in predetermined proportions. Based on this finding, the inventors have conducted further research and have completed the present invention.

[0019] That is, the present invention includes the following inventions. [1] A ceramic ceramic material comprising ZrO2, HfO2, a stabilizer capable of suppressing a phase transformation of zirconia, and Nb2O5 and / or Ta2O5; In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, The zirconia composite sintered body further contains a Group I element and TiO2. [2] The zirconia composite sintered body according to [1], wherein the TiO2 content is greater than 0 mass% and not more than 5.0 mass%, relative to 100 mass% of the total of ZrO2, HfO2, the stabilizer, Nb2O5 and Ta2O5. [3] The zirconia composite sintered body according to [1] or [2], wherein the content of the Group I element is more than 0 mol% and not more than 3 mol% relative to a total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. [4] The zirconia composite sintered body according to any one of [1] to [3], wherein the Group I element includes at least one element selected from the group consisting of Li, Na, and K. [5] When the content of the stabilizer is A mol%, and the total content of Nb2O5 and Ta2O5 is B mol%, The zirconia composite sintered body according to any one of [1] to [4], wherein A / B is 0.9 or more and 3 or less. [6] The zirconia composite sintered body according to any one of [1] to [5], wherein the stabilizer contains Y2O3 and / or CeO2. [7] The zirconia composite sintered body according to any one of [1] to [6], having a TiO2 content of 0.6% by mass or more and 4.3% by mass or less. [8] The zirconia composite sintered body according to any one of [1] to [7], having a biaxial bending strength measured in accordance with ISO 6872:2015 of 350 MPa or more. [9] The zirconia composite sintered body according to any one of [1] to [8], wherein the zirconia composite sintered body has an average crystal grain size of 0.5 to 5.0 μm.

[10] A ceramic ceramic material comprising ZrO2, HfO2, a stabilizer capable of suppressing a phase transformation of zirconia, and Nb2O5 and / or Ta2O5; In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, A step of producing a molded body using a raw material composition further containing a raw material compound of a Group I element and TiO2; and sintering the compact. A method for producing the zirconia composite sintered body according to [1].

[11] The raw material compound of the Group I element is a hydroxide and / or a salt of the Group I element, The method further includes a step of wet-mixing each of the raw materials of the raw material composition in a solvent containing water to obtain a raw material composition. A method for producing a zirconia composite sintered body according to

[10] .

[12] The method for producing a zirconia composite sintered body according to

[10] or

[11] , wherein in the raw material composition, the stabilizer includes a stabilizer that is not solid-dissolved in ZrO2 and HfO2.

[13] In the step of sintering the molded body, Sintering at 1300 to 1680°C; Including HIP processing at 1200℃ or higher. The method for producing the zirconia composite sintered body according to any one of

[10] to

[12] .

[14] After the HIP treatment, a step of heat treating at 1400°C or less in air or in an oxygen-rich atmosphere is included. A method for producing a zirconia composite sintered body according to

[13] . Effect of the Invention

[0020] According to the present invention, it is possible to provide a zirconia composite sintered body having strength and translucency suitable for dental use and excellent machinability. Furthermore, according to the present invention, a zirconia composite sintered body can be provided which can be machined in a sintered body state, the machining time is short, and wear of the machining tool can be suppressed. A large number of dental prostheses can be machined by continuous machining using a single machining tool (hereinafter also simply referred to as "continuous machining"), thereby providing a highly productive and economical zirconia composite sintered body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The zirconia composite sintered body of the present invention contains ZrO2, HfO2, a stabilizer capable of suppressing a phase transition of zirconia (hereinafter, also simply referred to as a "stabilizer"), and Nb2O5 and / or Ta2O5, In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, It further contains Group I elements and TiO2.

[0022] The zirconia composite sintered body of the present invention means a state in which ZrO2 particles (powder) are completely sintered (sintered state). In this specification, the upper and lower limits of the numerical ranges (contents of each component, ratios calculated from each component, values, and each physical property, etc.) can be appropriately combined. In this specification, the mechanical processing includes cutting and grinding. In addition, the mechanical processing may be either wet processing or dry processing, and is not particularly limited.

[0023] In this specification, the content of each component in the zirconia composite sintered body can be calculated from the amount of the raw material charged. In addition, the contents of the respective components ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 in the zirconia composite sintered body can also be measured by, for example, inductively coupled plasma (ICP) emission spectrometry, fluorescent X-ray analysis or the like. The content (mol%) of the Group I element is the external addition rate relative to the total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. Therefore, the content of the Group I element in the zirconia composite sintered body can be calculated by converting the amount (mass) of the raw material added at the time of addition into mol%. The content of TiO2 (mass%) is the external addition rate relative to the total of 100 mass% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. Therefore, the content of TiO2 in the zirconia composite sintered body can be calculated from the amount (mass) of the raw material added when it is added.

[0024] The zirconia composite sintered body of the present invention has strength and translucency suitable for dental use, and also has high machinability, so that it can be machined in the sintered body state. Although the reason is not clear, it is presumed as follows. In a zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of suppressing a phase transition of zirconia, and Nb2O5 and / or Ta2O5, it is presumed that the presence of Group I elements at the grain boundaries of zirconia particles reduces the grain boundary strength, thereby acting in a direction that makes it easier for the particles to peel off, making the material easier to cut and improving machinability. In a zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of suppressing the phase transition of zirconia, and Nb2O5 and / or Ta2O5, it is presumed that the presence of Group I elements at the interfaces (hereinafter also referred to as "grain boundaries") of zirconia particles reduces the strength of the grain boundaries, thereby acting in a direction that makes it easier for the particles to peel off, making the material easier to cut and improving machinability.

[0025] In addition, since Nb2O5 and / or Ta2O5 act in the direction of coarsening the microstructure and reducing the hardness in the zirconia composite sintered body, the group I elements and Nb2O5 and / or Ta2O5 act together to improve the machinability. Therefore, the group I elements and Nb2O5 and / or Ta2O5 act together to provide the strength required for artificial teeth while providing excellent machinability, and in addition to shortening the machining time, it is possible to suppress the wear of the machining tool, and the number of dental prostheses obtained by continuous processing using one machining tool can be increased, and it is presumed that the problems specific to continuous processing of sintered bodies can also be solved.

[0026] The zirconia composite sintered body of the present invention is presumed to have a structure containing zirconia particles containing ZrO2, HfO2, and a stabilizer capable of suppressing the phase transition of zirconia, an adhesive component containing ZrO2, HfO2, Nb2O5 and / or Ta2O5, and TiO2, and a release component containing a Group I element. TiO2 is mainly present in the grain boundaries together with the group I elements. By making TiO2 exist locally in each part of the grain boundaries, it is possible to create unevenness in the grain boundary strength as shown by the broken line, as opposed to the grain boundary strength weakened by the presence of the group I elements, and this makes it possible to improve the grain boundary strength while suppressing the decrease in the above-mentioned effect obtained by combining the group I elements with Nb2O5 and / or Ta2O5. Furthermore, TiO2 can improve the translucency when Nb2O5 and / or Ta2O5 are present. Therefore, it is presumed that according to the present invention, a zirconia composite sintered body having strength and translucency suitable for dental use and high machinability can be obtained.

[0027] In the zirconia composite sintered body of the present invention, the Group I element acts as an agent for imparting machinability as described above, and further does not impair strength and translucency.

[0028] In a preferred embodiment, the content of Group I elements contained in the zirconia composite sintered body of the present invention is preferably more than 0 mol% and not more than 3 mol%, and from the viewpoint of superior machinability and enabling a further increase in the number of dental prostheses that can be continuously machined with one machining tool, it is more preferable that it is 0.05 mol% or more and 3 mol% or less, and from the viewpoint of superior strength, it is even more preferable that it is 0.06 mol% or more and 2.5 mol% or less, particularly preferably 0.07 mol% or more and 1.0 mol% or less, and most preferably 0.08 mol% or more and 0.34 mol% or less. The above mentioned contents can be used as long as it is a Group I element. On the other hand, compared to Li, Na, K, Rb, Cs, and Fr have a higher atomic weight, and as the atomic weight increases, the force acting in the direction in which the particles are easily peeled off increases, and the content required to achieve the effects of the present invention tends to decrease. Therefore, the above-mentioned content is particularly suitable when the Group I element is K, Rb, Cs, or Fr. In another preferred embodiment, the content of Group I elements contained in the zirconia composite sintered body of the present invention is preferably more than 0 mol% and not more than 4.2 mol%, and from the viewpoint of being superior in machinability and enabling a further increase in the number of dental prostheses that can be continuously machined with one machining tool, the content is more preferably 0.05 mol% to 4.0 mol%, even more preferably 0.06 mol% to 3.8 mol%, particularly preferably 0.07 mol% to 3.6 mol%, and most preferably 0.08 mol% to 3.5 mol%. The above mentioned contents can be used as long as it is a Group I element. For example, when the Group I element is Li and / or Na, the content of the Group I element contained in the zirconia composite sintered body of the present invention may be the above-mentioned content. The content of the Group I element in any of the embodiments can be appropriately used as long as the effects of the present invention can be obtained, taking into consideration the contents of other components. In another preferred embodiment, the content of Group I elements contained in the zirconia composite sintered body of the present invention may be more than 3 mol % and not more than 4.2 mol %, as long as the effects of the present invention are exhibited.

[0029] Examples of Group I elements include Li, Na, K, Rb, Cs, and Fr. The Group I elements may be used alone or in combination of two or more. In one embodiment, the group I element includes one element selected from the group consisting of Li, Na, and K.

[0030] In the zirconia composite sintered body of the present invention, the total content of ZrO2 and HfO2 is 78 to 97.5 mol% in a total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5, and from the viewpoint of superior translucency and strength, it is preferably 79 mol% or more and 96 mol% or less, more preferably 80 mol% or more and 94 mol% or less, and even more preferably 81 mol% or more and 93 mol% or less.

[0031] Examples of stabilizers capable of suppressing the phase transition of zirconia include calcium oxide (CaO), magnesium oxide (MgO), yttrium oxide (Y2O3), cerium oxide (CeO2), scandium oxide (Sc2O3), lanthanum oxide (La2O3), erbium oxide (Er2O3), praseodymium oxide (Pr2O3, Pr6O 11 Examples of the oxide include samarium oxide (Sm2O3), europium oxide (Eu2O3), thulium oxide (Tm2O3), gallium oxide (Ga2O3), indium oxide (In2O3) and ytterbium oxide (Yb2O3), and Y2O3 (yttria) and / or CeO2 are preferred because they provide better effects of the present invention and are particularly aesthetically pleasing. The stabilizers may be used alone or in combination of two or more.

[0032] As described above, the Group I element and Nb2O5 and / or Ta2O5 act together, and these components, as well as TiO2, do not impair the effect of the stabilizer, so the stabilizer is not particularly limited and the effects of the present invention are achieved.

[0033] In the zirconia composite sintered body of the present invention, the content of the stabilizer capable of suppressing the phase transition of zirconia is 1 to 12 mol%, preferably 2 mol% to 10 mol%, more preferably 3 mol% to 8 mol%, and even more preferably 3.5 mol% to 7.5 mol%, in terms of superior translucency and strength, in a total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. If the content of the stabilizer exceeds 12 mol%, sufficient machinability is difficult to obtain. In one preferred embodiment, a zirconia composite sintered body is mentioned in which a stabilizer capable of suppressing a phase transition of zirconia contains Y2O3 and / or CeO2, and the total content of Y2O3 and CeO2 is 2 mol% or more and 10 mol% or less. Another preferred embodiment is a zirconia composite sintered body in which the stabilizer capable of suppressing the phase transition of zirconia contains Y2O3 and the content of Y2O3 is 2 mol % or more and 10 mol % or less. In any of the above-described embodiments, the content of Y2O3 and CeO2 can be appropriately changed within the range described in this specification. For example, in order to obtain better translucency and strength, the total content of Y2O3 and CeO2 may be 2.5 mol% or more and 10 mol% or less, or 3 mol% or more and 9 mol% or less.

[0034] In the zirconia composite sintered body of the present invention, the total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, preferably 1.5 mol% to 8.5 mol%, in the total of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 being 100 mol%, and more preferably 2.5 mol% to 8 mol%, and even more preferably 3 mol% to 7 mol% in terms of acting together with the group I elements and having better machinability. If the total content of Nb2O5 and Ta2O5 is less than 1 mol%, it is difficult to obtain sufficient machinability. Also, if the total content of Nb2O5 and Ta2O5 exceeds 9 mol%, chipping occurs in the obtained zirconia composite sintered body, making it difficult to obtain sufficient physical properties.

[0035] As described above, Nb2O5 and Ta2O5 act to coarsen the microstructure and reduce hardness, and act together with the Group I elements to impart excellent machinability. In addition, by interacting with other components added to the zirconia composite sintered body (e.g., TiO2, Al2O3) and by applying HIP, the sintered density can be maximized, ensuring the aesthetics of natural teeth.

[0036] The content of each of the above-mentioned ZrO2, HfO2, stabilizer, Nb2O5, and Ta2O5 components is the percentage relative to the total of 100 mol% of ZrO2, HfO2, stabilizer, Nb2O5, and Ta2O5, and the total of ZrO2, HfO2, stabilizer, Nb2O5, and Ta2O5 does not exceed 100 mol%. For example, when the raw material composition contains Nb2O5 but does not contain Ta2O5, the content of each of the ZrO2, HfO2, stabilizer, and Nb2O5 components means the content percentage relative to the total of 100 mol% of ZrO2, HfO2, stabilizer, and Nb2O5.

[0037] Furthermore, when the content of the stabilizer is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %, the ratio A / B is preferably 0.9 to 3 inclusive from the viewpoint of machinability, and more preferably 0.95 to 2 inclusive, and even more preferably 1 to 1.6 inclusive, since this enhances the effect of the Group I element and Nb2O5 and / or Ta2O5 acting together, thereby imparting better machinability, suppressing wear of the machining tool, and enabling a further increase in the number of dental prostheses obtained by continuous machining using one machining tool.

[0038] In the zirconia composite sintered body of the present invention, the content of TiO2 is preferably more than 0 mass% and not more than 5.0 mass%, more preferably 0.01 mass% or more and not more than 4.5 mass% or less, relative to the total 100 mass% of ZrO2, HfO2, the stabilizer capable of suppressing the phase transition of zirconia, Nb2O5, and Ta2O5. Since TiO2 acts as an integrated element when combined with a Group I element and provides superior strength, the content of TiO2 is further preferably 0.6 mass% or more and 4.3 mass% or less, particularly preferably 0.7 mass% or more and 3.7 mass% or less, and most preferably 2.5 mass% or more and 3.5 mass% or less.

[0039] In one preferred embodiment, the composition includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia, and Nb2O5 and / or Ta2O5, In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, Further comprising a Group I element and TiO2, the stabilizer comprises Y2O3 and / or CeO2; The TiO2 content is 0.6% by mass or more and 4.3% by mass or less, The content of the Group I element is more than 0 mol% and 3 mol% or less with respect to a total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5, When the content of the stabilizer is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %, the zirconia composite sintered body has an A / B ratio of 0.9 or more and 3 or less.

[0040] In the preferred embodiment described above, as described above, the total content of ZrO2 and HfO2, the type and content of the stabilizer, the total content of Nb2O5 and Ta2O5, the type and content of Group I elements, the content of TiO2, and the ratio A / B can be changed as appropriate.

[0041] The average crystal grain size of the zirconia composite sintered body of the present invention is preferably 0.5 to 5.0 μm, more preferably 0.5 to 4.5 μm from the viewpoint of superior machinability, and further preferably 1.0 to 4.0 μm. The method for measuring the average crystal grain size is as described in the Examples below. The average crystal grain size can be measured by adjusting the number of particles so that the number of particles contained in one field of view of an SEM photograph is about 50 or 100, in the method described in the Examples.

[0042] The density of the zirconia composite sintered body is set to 5.5 g / cm because the higher the density, the fewer the internal voids, the less light scattering, the improved translucency, and the improved strength. 3 It is preferable that the content is 5.7 g / cm or more. 3 More preferably, it is 5.9 g / cm or more. 3 More preferably, it is equal to or greater than this. It is particularly preferable that the zirconia composite sintered body contains substantially no voids. The density of the compound sintered body can be calculated by (mass of the compound sintered body) / (volume of the compound sintered body).

[0043] Another embodiment of the present invention is a ceramic ceramic comprising ZrO2, HfO2, a stabilizer capable of inhibiting a phase transformation of zirconia, and Nb2O5 and / or Ta2O5, In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, A step of producing a molded body using a raw material composition further containing a raw material compound of a Group I element and TiO2; and sintering the green body.

[0044] The raw material composition of the zirconia composite sintered body includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transition of zirconia, Nb2O5 and / or Ta2O5, a raw material compound of a Group I element, and TiO2. The raw material composition of the zirconia composite sintered body may be in a dry state, or may be in a state containing a liquid or in a state contained in a liquid. The raw material composition may be in the form of, for example, a powder, granules or granulated material, a paste, a slurry, or the like.

[0045] The raw material composition contains a raw material compound of a Group I element so that the resulting zirconia composite sintered body contains an element of Group I. Examples of the raw material compound of the Group I element include hydroxides and / or salts of the Group I element.

[0046] Examples of hydroxides of Group I elements include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, and francium hydroxide. Examples of salts of Group I elements include carbonates and hydrogen carbonates. Examples of carbonates of Group I elements include lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, francium carbonate, and cesium carbonate. Group I hydrogen carbonates include lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, rubidium hydrogen carbonate, francium hydrogen carbonate, and cesium hydrogen carbonate. The hydroxides and salts of Group I elements may each be used alone or in combination of two or more.

[0047] For ZrO2 and HfO2, commercially available zirconia powder can be used. Examples of commercially available products include zirconia powder (trade name "Zpex (registered trademark)" (Y2O3 content: 3 mol%), "Zpex (registered trademark) 4" (Y2O3 content: 4 mol%), "Zpex (registered trademark) 4" (Y2O3 content: 4 mol%), Smile (registered trademark) (Y2O3 content: 5.5 mol%), TZ-3Y (Y2O3 content: 3 mol%), TZ-3YS (Y2O3 content: 3 mol%), TZ-4YS (Y2O3 content: 4 mol%), TZ-6Y (Y2O3 content: 6 mol%), TZ-6YS (Y2O3 content: 6 mol%), TZ-8YS (Y2O3 content: 8 mol%), TZ-10YS (Y2O3 content: 10 mol%), TZ-3Y-E (Y2O3 content: 3 mol%) "TZ-3YS-E" (Y2O3 content: 3 mol%), "TZ-3YB-E" (Y2O3 content: 3 mol%), "TZ-3YSB-E" (Y2O3 content: 3 mol%), "TZ-3YB" (Y2O3 content: 3 mol%), "TZ-3YSB" (Y2O3 content: 3 mol%), "TZ-3Y20AB" (Y2O3 content: 3 mol%), "TZ-8YSB" (Y2O3 content: 8 mol%), "TZ-0" (Y2O3 content: 0 mol%); all manufactured by Tosoh Corporation. The commercially available zirconia powder also contains HfO2. Commercially available products that also contain Y2O3 can also be used. As the zirconia powder, the raw material composition of the present invention can also use zirconia powder in which Y2O3 is uniformly dispersed and solid-solved, such as the commercially available TZ series (part of the product name includes "TZ").

[0048] There are no particular limitations on the method for producing the zirconia powder, and any known method can be used, such as a breakdown process in which coarse particles are pulverized into fine powder, or a building-up process in which zirconia powder is synthesized from atoms or ions through a nucleation and growth process.

[0049] The type of zirconia powder in the raw material composition is not particularly limited, and when the zirconia powder contains ZrO2 and HfO2 and does not contain a stabilizer, or when the content of the stabilizer is increased as necessary, stabilizer particles can be added separately. The stabilizer particles are not particularly limited as long as the content of the stabilizer contained in the zirconia composite sintered body can be adjusted to the above-mentioned predetermined range. The particles of the stabilizer may be, for example, a commercially available product, or a powder of the commercially available product may be ground in a known grinding and mixing device (such as a ball mill) before use.

[0050] The stabilizer may be either one that is not solid-dissolved in ZrO2 and HfO2 or one that is solid-dissolved in ZrO2 and HfO2. In a preferred embodiment, the method for producing a zirconia composite sintered body includes a stabilizer (preferably, Y2O3) that is not solid-dissolved in ZrO2 and HfO2, because this is one factor that makes it easy to obtain a target zirconia composite sintered body in the raw material composition. The fact that the stabilizer includes one that is not solid-dissolved in zirconia can be confirmed, for example, by an X-ray diffraction (XRD) pattern.

[0051] When a peak attributable to the stabilizer is confirmed in the XRD pattern of the raw material composition or the molded body, it means that the stabilizer is present in the raw material composition or the molded body without being dissolved in ZrO2 and HfO2. When the entire amount of the stabilizer is dissolved in ZrO2 and HfO2, basically, no peaks derived from the stabilizer are observed in the XRD pattern. However, depending on the conditions such as the crystal state of the stabilizer, even if there is no stabilizer peak in the XRD pattern, the stabilizer may not be dissolved in ZrO2 and HfO2.

[0052] The case where the stabilizer includes a stabilizer that is not solid-dissolved in ZrO2 and HfO2 will be described below by taking an example in which the stabilizer is yttria.

[0053] In the raw material composition or molded body of the present invention, the abundance rate f of yttria that is not dissolved in ZrO2 and HfO2 (hereinafter sometimes referred to as "undissolved yttria") is y can be calculated based on the following formula (1). f y =I 29 / (I 28 +I 29 +I 30 ) x 100 (In the formula, f y represents the percentage of undissolved yttria (%). In the XRD measurement, I 28 represents the integrated intensity of the peak at 2θ = 28° where the main monoclinic peak appears, and I 29 represents the intensity of the peak at 2θ = 29° where the main peak of yttria appears, and I 30 represents the integrated intensity of the peak near 2θ=30° where the main peak of the tetragonal or cubic crystal system appears.)

[0054] In addition, when a stabilizer other than yttria is used, I 29 By substituting the peak of another stabilizer instead of yttria, the above formula can also be applied to calculate the undissolved fraction of stabilizers other than yttria.

[0055] Undissolved yttria abundance f yFrom the viewpoint of facilitating the production of the desired zirconia composite sintered body, the content of undissolved yttria f is preferably greater than 0%, more preferably 1% or more, even more preferably 2% or more, and particularly preferably 3% or more. y The upper limit may be, for example, 25% or less, but preferably depends on the content of yttria in the raw material composition or the molded body.

[0056] For example, when the content of yttria in the raw material composition or molded article of the present invention is 3 mol % or more and 8 mol % or less, the following applies. When the yttria content is 3 mol% or more and less than 4.5 mol%, f y When the yttria content is 4.5 mol% or more and less than 5.8 mol%, f y When the yttria content is 5.8 mol% or more and 8 mol% or less, f y may be no more than 25%.

[0057] For example, when the yttria content is 3 mol% or more and less than 4.5 mol%, f y is preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, and particularly preferably 5% or more. When the yttria content is 4.5 mol% or more and less than 5.8 mol%, f y is preferably 3% or more, more preferably 4% or more, even more preferably 5% or more, even more preferably 6% or more, and particularly preferably 7% or more. When the yttria content is 5.8 mol% or more and 8 mol% or less, f y is preferably 4% or more, more preferably 5% or more, even more preferably 6% or more, even more preferably 7% or more, and particularly preferably 8% or more.

[0058] In the raw material composition or molded body of the present invention, the entire stabilizer does not have to be solid-dissolved in ZrO2 and HfO2. In the present invention, the stabilizer being solid-dissolved means, for example, that an element (atom) contained in the stabilizer is solid-dissolved in ZrO2 and HfO2.

[0059] The Nb2O5 and / or Ta2O5 added to the raw material composition of the present invention is not particularly limited as long as the content of Nb2O5 and / or Ta2O5 contained in the zirconia composite sintered body can be adjusted to the above-mentioned range. Nb2O5 and / or Ta2O5 are not particularly limited, and for example, commercially available products may be used, or the powder of the commercially available product may be crushed with a known crushing and mixing device (such as a ball mill) before use.

[0060] An example of a process for preparing the raw material composition is a method in which the raw materials of the raw material composition (ZrO2, HfO2, a stabilizer, Nb2O5 and / or Ta2O5, a raw material compound of a Group I element (e.g., a hydroxide and / or a salt of a Group I element), and TiO2) are wet-mixed in a solvent containing water to obtain the raw material composition.

[0061] The shape of TiO2 added to the raw material composition is not particularly limited and may be granular, acicular, or the like. However, granular TiO2 is preferred because it has excellent machinability and makes it easier to increase the number of TiO2 particles obtained by continuous processing of the sintered body.

[0062] When the TiO2 added to the raw material composition is granular TiO2, the average particle size of TiO2 is not particularly limited as long as the effect of the present invention is achieved since the raw materials are mixed and then pulverized, and may be 7 nm or more or 100 μm or less. The reason that the average particle size of the granular TiO2 is not limited is that when mixed with powders of other raw material components, it is pulverized until it has a desired average particle size, so there is no reason to limit the granular TiO2 added as a raw material. The average particle size of TiO2 is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more, from the viewpoint of easily obtaining excellent machinability and easily increasing the number of pieces obtained by continuous processing of the sintered body. Also, the average particle size of TiO2 is preferably 50 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less, from the viewpoint of easily obtaining excellent machinability and easily increasing the number of pieces obtained by continuous processing of the sintered body.

[0063] The average particle size of TiO2 can be determined by the laser diffraction scattering method or by observing the particles under an electron microscope. Specifically, the laser diffraction scattering method is convenient for measuring particle sizes of 0.1 μm or more, while electron microscope observation is convenient for measuring the particle size of ultrafine particles less than 0.1 μm. 0.1 μm is the measurement value obtained by the laser diffraction scattering method. In the case of particles that are made up of agglomerated primary particles, there are average particle sizes of the primary particles and the secondary particles, but the average particle size of the filler is the average particle size of the secondary particles, which have a larger particle size.

[0064] Specifically, the laser diffraction scattering method can be performed by, for example, using a laser diffraction particle size distribution analyzer (SALD-2300, manufactured by Shimadzu Corporation) and measuring on a volume basis using a 0.2% aqueous solution of sodium hexametaphosphate as a dispersion medium.

[0065] Specifically, electron microscope observation can be performed by taking a photograph of the particles with an electron microscope (S-4000 model, manufactured by Hitachi, Ltd.) and measuring the particle diameters of the particles (200 or more) observed within a unit field of view of the photograph using image analysis type particle size distribution measurement software (Mac-View (manufactured by Mountec Co., Ltd.)). At this time, the particle diameter is determined as the arithmetic mean value of the longest and shortest lengths of the particles, and the average particle diameter is calculated from the number of particles and their particle diameters.

[0066] The method for wet-mixing the raw materials in a solvent containing water is not particularly limited. For example, the raw materials may be wet-pulverized and mixed in a known pulverizing and mixing device (such as a ball mill) to form a slurry, and then the slurry may be dried and granulated to produce a granular raw material composition.

[0067] In the wet mixing step, additives such as a binder, a plasticizer, a dispersant, an emulsifier, an antifoaming agent, a pH adjuster, a lubricant, etc. may be further included. Each of the additives may be used alone or in combination of two or more kinds.

[0068] The binder may be added to a milled slurry of a primary powder of a mixture of ZrO2, HfO2, Y2O3, Nb2O5 and / or Ta2O5, hydroxides and / or salts of Group I elements, and TiO2 in water.

[0069] The binder is not particularly limited, and known binders can be used. Examples of binders include polyvinyl alcohol binders, acrylic binders, wax binders (paraffin wax, etc.), methyl cellulose, carboxymethyl cellulose, polyvinyl butyral, polymethyl methacrylate, ethyl cellulose, polyethylene, polypropylene, ethylene-vinyl acetate copolymers, polystyrene, atactic polypropylene, and methacrylic resins.

[0070] Examples of the plasticizer include polyethylene glycol, glycerin, propylene glycol, and dibutyl phthalate.

[0071] Examples of dispersants include ammonium polycarboxylate (e.g., triammonium citrate), ammonium polyacrylate, acrylic copolymer resin, acrylic acid ester copolymer, polyacrylic acid, bentonite, carboxymethyl cellulose, anionic surfactants (e.g., polyoxyethylene alkyl ether phosphates such as polyoxyethylene lauryl ether phosphate), nonionic surfactants, olein glyceride, amine salt surfactants, oligosaccharide alcohols, and stearic acid.

[0072] Examples of the emulsifier include alkyl ethers, phenyl ethers, and sorbitan derivatives.

[0073] Examples of the defoaming agent include alcohol, polyether, silicone, wax, and the like.

[0074] Examples of pH adjusters include ammonia, ammonium salts (including ammonium hydroxides such as tetramethylammonium hydroxide), and the like.

[0075] Examples of the lubricant include polyoxyethylene alkyl ether and wax.

[0076] The solvent used in the wet mixing is not particularly limited as long as it contains water, and an organic solvent may be used, a mixed solvent of water and an organic solvent may be used, or only water may be used. Examples of the organic solvent include ketone solvents such as acetone and ethyl methyl ketone; alcohol solvents such as ethanol, 1-propanol, 2-propanol, 2-methyl-2-propanol, glycerin, diglycerin, polyglycerin, propylene glycol, dipropylene glycol, polypropylene glycol, ethylene glycol, diethylene glycol, polyethylene glycol, polyethylene glycol monomethyl ether, 1,2-pentanediol, 1,2-hexanediol, and 1,2-octanediol.

[0077] The raw material composition of the zirconia composite sintered body used in the present invention may contain other components in addition to ZrO2, Y2O3, Nb2O5, Ta2O5, hydroxides and / or salts of Group I elements, and TiO2, as long as the effects of the present invention are achieved. Examples of the other components include colorants (pigments and composite pigments), fluorescent agents, SiO2, etc. Each of the other components may be used alone, or two or more may be mixed.

[0078] Examples of the pigment include oxides of at least one element selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr2O3, etc.), and oxides of at least one element selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, and Tb are preferred, and oxides of at least one element selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd, and Tb are more preferred. However, Y2O3 and CeO2 may be excluded from the pigment.

[0079] Examples of the composite pigment include (Zr,V)O2, Fe(Fe,Cr)2O4, (Ni,Co,Fe)(Fe,Cr)2O4·ZrSiO4, and (Co,Zn)Al2O4.

[0080] Examples of the fluorescent agent include Y2SiO5:Ce, Y2SiO5:Tb, (Y,Gd,Eu)BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, and BaMgAl 10 O 17 :Eu, etc.

[0081] Next, the obtained raw material composition is molded to produce a molded body. The molding method is not particularly limited, and a known method (for example, press molding, etc.) can be used.

[0082] In the case of producing a zirconia molded body by a method having a step of press-molding a raw material composition, the specific method of press molding is not particularly limited, and can be performed using a known press molding machine. Specific examples of the press molding method include uniaxial pressing.

[0083] The pressing pressure is set to an appropriate optimum value depending on the size, open porosity, biaxial bending strength, and particle size of the raw material powder of the target molded body, and is usually 5 MPa to 1000 MPa. By increasing the pressing pressure during molding in the above-mentioned manufacturing method, the pores of the obtained molded body are filled more, the open porosity can be set low, and the density of the molded body can be increased. In addition, in order to increase the density of the obtained zirconia molded body, a cold isostatic pressing (CIP) treatment may be further performed after uniaxial pressing.

[0084] Next, the resulting green body is sintered. The term "molded body" refers to a body that has not yet reached a semi-sintered state (calcined state) or a sintered state. In other words, the molded body is distinguished from the calcined body and the sintered body in that the molded body is a body that has been molded and then not sintered. The sintering temperature (maximum sintering temperature) for obtaining the zirconia composite sintered body is, for example, preferably 1300°C or higher, more preferably 1350°C or higher, even more preferably 1400°C or higher, even more preferably 1450°C or higher, and particularly preferably 1500°C or higher. The sintering temperature is, for example, preferably 1680°C or lower, more preferably 1650°C or lower, and even more preferably 1600°C or lower. In the method for producing the zirconia composite sintered body of the present invention, it is preferable to sinter the molded body at a maximum sintering temperature of 1300 to 1680°C. The maximum sintering temperature is preferably a temperature in the atmosphere.

[0085] The holding time (holding time) at the maximum sintering temperature depends on the temperature, but is preferably 30 hours or less, more preferably 20 hours or less, even more preferably 10 hours or less, even more preferably 5 hours or less, particularly preferably 3 hours or less, and most preferably 2 hours or less. Furthermore, the holding time can be 25 minutes or less, 20 minutes or less, or 15 minutes or less. Moreover, the holding time is preferably 1 minute or more, more preferably 5 minutes or more, and even more preferably 10 minutes or more. According to the manufacturing method of the present invention, a zirconia composite sintered body excellent in bending strength, translucency, and machinability can be produced according to the content of the stabilizer. Moreover, the sintering time may be shortened as long as the effect of the present invention can be obtained. By shortening the sintering time, it is possible to increase production efficiency and reduce energy costs.

[0086] In the method for producing a zirconia composite sintered body of the present invention, when the molded body is sintered, the heating rate is not particularly limited, and is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and even more preferably 0.5°C / min or more. The heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and even more preferably 20°C / min or less. By setting the heating rate to the above lower limit or more, productivity is improved.

[0087] A general dental zirconia firing furnace can be used in the step of sintering the molded body. Commercially available dental zirconia firing furnaces may be used. Examples of commercially available products include Noritake Katana (registered trademark) F-1, F-1N, and F-2 (all manufactured by SK Medical Electronics Co., Ltd.).

[0088] Furthermore, the step of sintering the compact preferably includes a step of hot isostatic pressing (HIP) treatment in addition to the sintering at the maximum sintering temperature described above. The HIP treatment can further improve the translucency and strength of the zirconia composite sintered compact.

[0089] Hereinafter, the sintered body obtained by sintering at the above-mentioned maximum sintering temperature is referred to as a "primary sintered body", and the sintered body after the HIP treatment is referred to as a "HIP-treated sintered body".

[0090] The HIP treatment can be carried out using a known hot isostatic press (HIP) device.

[0091] The temperature of the HIP treatment is not particularly limited, but since a dense zirconia composite sintered body with high strength can be obtained, the HIP temperature is preferably 1200° C. or higher, more preferably 1300° C. or higher, and even more preferably 1400° C. or higher. The HIP temperature is preferably 1700° C. or lower, more preferably 1650° C. or lower, and even more preferably 1600° C. or lower.

[0092] In the manufacturing method of the zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP pressure is not particularly limited, and since a dense sintered body with high strength can be obtained, the HIP pressure is preferably 100 MPa or more, more preferably 125 MPa or more, and even more preferably 130 MPa or more. In addition, the upper limit of the HIP pressure is not particularly limited, but it can be, for example, 400 MPa or less, 300 MPa or less, or even 200 MPa or less.

[0093] In the method for producing a zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the heating rate is not particularly limited, and is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and even more preferably 0.5°C / min or more. The heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and even more preferably 20°C / min or less. By setting the heating rate at or above the lower limit, productivity is improved.

[0094] In the method for producing the zirconia composite sintered body of the present invention, when the primary sintered body is subjected to the HIP treatment, the HIP time is not particularly limited, and since a dense zirconia composite sintered body having high strength can be obtained, the HIP treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. Also, the HIP treatment time is preferably 10 hours or less, more preferably 6 hours or less, and even more preferably 3 hours or less.

[0095] In the method for producing a zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the pressure medium is not particularly limited, and from the viewpoint of having little effect on zirconia, the pressure medium can be at least one selected from the group consisting of oxygen, oxygen containing 3% hydrogen, air, and an inert gas (e.g., nitrogen, argon, etc.). When the primary sintered body is subjected to the HIP treatment in an oxygen mixed gas atmosphere, the oxygen concentration is not particularly limited, but can be, for example, more than 0% and 20% or less. When an oxygen mixed gas is used, at least one inert gas (eg, nitrogen, argon, etc.) can be selected as the gas other than oxygen.

[0096] In the manufacturing method of the zirconia composite sintered body of the present invention, if the HIP treatment is performed in a reducing atmosphere, such as by using an inert gas, blackening may occur due to oxygen defects. In that case, in order to remove the blackening, it is preferable to include a step of heat treatment in air or in an oxygen-rich atmosphere at 1650°C or less (hereinafter also referred to as "tempering treatment") after the HIP treatment step, and from the viewpoint of efficient heat treatment, it is more preferable to perform the heat treatment in an oxygen-rich atmosphere. An oxygen-rich atmosphere means that the oxygen concentration is higher than that of air. The oxygen-rich atmosphere is not particularly limited as long as the oxygen concentration is more than 21% and less than 100%, and can be appropriately selected from this range. For example, the oxygen concentration may be 100%.

[0097] The zirconia composite sintered body of the present invention is not particularly limited as long as it exhibits the effects of the present invention, and may be a primary sintered body, a HIP-treated sintered body, or a sintered body after tempering. As a preferred embodiment, there is mentioned a zirconia composite sintered body which is a sintered body after tempering treatment.

[0098] The temperature of the heat treatment in air or in an oxygen-rich atmosphere can be appropriately changed depending on the aesthetics of the zirconia composite sintered body (for example, the shade of a dental prosthesis). In a preferred embodiment, the temperature of the heat treatment in the air or in an oxygen-rich atmosphere is preferably 1650°C or less, more preferably 1600°C or less, and even more preferably 1550°C or less, from the viewpoint of the aesthetics of the zirconia composite sintered body. In another preferred embodiment, the temperature of the heat treatment in the air or in an oxygen-rich atmosphere is preferably 1400°C or less, more preferably 1300°C or less, and even more preferably 1200°C or less, from the viewpoint of the aesthetics of the zirconia composite sintered body. Furthermore, in any embodiment, the temperature of the heat treatment is preferably 500° C. or higher, more preferably 600° C. or higher, and even more preferably 700° C. or higher.

[0099] A general dental zirconia firing furnace can be used for the tempering treatment. Commercially available dental zirconia firing furnaces may be used. Examples of commercially available products include Noritake Katana (registered trademark) F-1, F-1N, and F-2 (all manufactured by SK Medical Electronics Co., Ltd.).

[0100] Although the zirconia composite sintered body of the present invention is a sintered body, it has excellent machinability, so there is no need to machine the semi-sintered calcined body in the form of a mill blank and then sinter it to form a sintered body. On the other hand, the method for producing the zirconia composite sintered body may also be a method in which a molded body obtained by using the raw material composition is calcined to produce a calcined body in a semi-sintered state, and the unprocessed calcined body is mechanically processed to produce a sintered body.

[0101] In another embodiment, the method includes the steps of: preparing a molded body using the raw material composition; calcining the obtained molded body to obtain a calcined zirconia body (calcination step); and sintering the calcined zirconia body. A method for producing a zirconia composite sintered body can be mentioned.

[0102] In order to ensure blocking, the firing temperature (calcination temperature) in the calcination step is, for example, preferably 800° C. or higher, more preferably 900° C. or higher, and even more preferably 950° C. or higher. The calcination temperature is, for example, preferably 1200° C. or lower, more preferably 1150° C. or lower, and further preferably 1100° C. or lower. The calcination temperature is, for example, preferably 800° C. to 1200° C. At such a calcination temperature, it is considered that the dissolution of the stabilizer does not progress significantly in the calcination step.

[0103] The zirconia calcined body of the present invention means a body in which ZrO2 particles are necked (adhered) to each other and the ZrO2 particles (powder) are in a state where they are not completely sintered (semi-sintered state).

[0104] The density of the calcined zirconia body is 2.7 g / cm 3 The density of the calcined zirconia body is preferably 4.0 g / cm 3 Less than 3.8 g / cm is preferred. 3 Less than 3.6 g / cm is more preferable. 3 The following is even more preferable. When the density is within this range, processing can be easily performed. The density of the calcined body can be calculated, for example, by dividing the mass of the calcined body by the volume of the calcined body.

[0105] The three-point bending strength of the zirconia calcined body is preferably from 15 to 70 MPa, more preferably from 18 to 60 MPa, and even more preferably from 20 to 50 MPa. The bending strength can be measured using a test piece having a thickness of 5 mm, a width of 10 mm, and a length of 50 mm, in accordance with ISO 6872:2015, except for the size of the test piece. The face of the test piece and the C face (the face of the test piece with the corners chamfered at an angle of 45°) are surface-finished in the longitudinal direction with 600-grit sandpaper. The test piece is arranged so that the widest face faces vertically (load direction). In the bending test measurement, the span is 30 mm, and the crosshead speed is 1.0 mm / min.

[0106] The step of sintering the zirconia calcined body can be carried out by the same method and under the same conditions (temperature, pressure, etc.) as the step of sintering the molded body described above. Therefore, in the embodiment of the production method using the zirconia calcined body, the "molded body" can be read as the "calcined body".

[0107] The zirconia composite sintered body of the present invention has excellent strength. The biaxial bending strength of the zirconia composite sintered body of the present invention is preferably 350 MPa or more, more preferably 400 MPa or more, even more preferably 450 MPa or more, even more preferably 450 MPa or more, and particularly preferably 500 MPa or more. When the zirconia composite sintered body of the present invention has such a biaxial bending strength, it is possible to suppress fracture in the oral cavity when used as a dental prosthesis, for example. There is no particular limit to the upper limit of the biaxial bending strength, but the biaxial bending strength can be, for example, 1200 MPa or less, or even 1000 MPa or less. The biaxial bending strength of the zirconia composite sintered body can be measured in accordance with ISO 6872:2015.

[0108] The zirconia composite sintered body of the present invention preferably has high translucency. The translucency can be evaluated by ΔL*. Specifically, regarding the translucency, the zirconia composite sintered body of the present invention preferably has ΔL* of 10 or more at a diameter of 15 mm and a thickness of 1.2 mm, more preferably 12 or more, even more preferably 13 or more, and particularly preferably 14 or more. When the ΔL* is within the above range, a zirconia composite sintered body with high translucency can be obtained.

[0109] ΔL* means the difference between the lightness (first L* value) on a white background and the lightness (second L* value) on a black background for the same sample. Specifically, it means the difference between the L* value on a white background (JIS Z 8781-4:2013 Colorimetry-Part 4: CIE 1976 L*a*b* color space) and the L* value on a black background. The white background means the white part of the hiding ratio test paper described in JIS K 5600-4-1:1999 Part 4 Section 1, and the black background means the black part of the hiding ratio test paper.

[0110] There is no particular upper limit to ΔL*, but it can be, for example, 25 or less, and from the standpoint of aesthetics, even 20 or less.

[0111] In addition, ΔL* of a zirconia composite sintered body having a diameter of 15 mm and a thickness of 1.2 mm can be measured using a spectrophotometer, for example, a dental color measuring device ("Crystal Eye CE100-CE / JP", 7-band LED light source, analysis software "Crystal Eye" (manufactured by Olympus Corporation)).

[0112] Examples of dental prostheses manufactured from the zirconia composite sintered body of the present invention include crown restorations such as inlays, onlays, veneers, crowns, core-integrated crowns, and bridges, as well as abutments, dental posts, dentures, denture bases, and implant parts (fixtures, abutments). The machining is preferably performed using a commercially available dental CAD / CAM system. Examples of such CAD / CAM systems include the CEREC system manufactured by Dentsply Sirona Dental Systems Inc. and the Katana (registered trademark) system manufactured by Kuraray Noritake Dental Co., Ltd.

[0113] Furthermore, the zirconia composite sintered body of the present invention can be used for applications other than dental applications, and is particularly suitable for use in zirconia members that require a unique or complex shape and strength. Compared with sintered bodies produced only by existing manufacturing methods (injection molding, CIP, casting, 3D printing, etc.), the zirconia composite sintered body of the present invention can be processed as it is. Therefore, for example, it is economical when a desired zirconia part can be obtained in a short time, and in the case of a complex-shaped part that is difficult to produce by a conventional manufacturing method, it is possible to obtain a zirconia part that maintains high strength because it is not necessary to obtain multiple parts by mechanical fitting. Furthermore, since the sintered body can be processed as it is, when dimensional accuracy is required, a sintering process is not required, and since there is no uneven firing shrinkage, a zirconia part can be obtained with high accuracy. Specifically, it can also be used as a method for manufacturing parts for jewelry applications, engine parts and interior parts for mobility such as aircraft and automobiles, frame materials for display panels, building parts, electrical appliance parts, household goods parts, and toys. The zirconia member may also be fitted with a different material to be used as a composite member.

[0114] The present invention includes embodiments in which all or part of the above configurations are combined in various ways within the scope of the technical idea of ​​the present invention, as long as the effects of the present invention are achieved. EXAMPLES

[0115] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples, and many modifications within the scope of the technical concept of the present invention are possible by those having ordinary skill in the art. In the following examples and comparative examples, the average particle size refers to the average primary particle size, which can be determined by a laser diffraction scattering method. Specifically, it can be measured on a volume basis using a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) with a 0.2% aqueous solution of sodium hexametaphosphate as a dispersion medium.

[0116] [Examples 1 to 34 and Comparative Examples 1 to 8] The measurement samples of each of the Examples and Comparative Examples were prepared through the steps of preparing a granular raw material composition, preparing a compact, and preparing a sintered body (preparation of a primary sintered body, HIP treatment, and tempering treatment).

[0117] [Preparation of granular raw material composition] In order to prepare the granular raw material composition of each Example and Comparative Example, commercially available ZrO2 powder, Y2O3 powder, Nb2O5 powder, Ta2O5 powder, TiO2 powder, and raw material compounds of group I elements were mixed to have the compositions shown in Tables 1 to 3, water was added to prepare a slurry, and the mixture was wet-pulverized and mixed in a ball mill until the average particle diameter was 0.13 μm or less. After adding a binder to the pulverized slurry, the mixture was dried with a spray dryer to prepare a granular raw material composition (hereinafter, also simply referred to as "raw material composition"), which was used in the manufacture of a molded body described below. The average particle diameter was measured on a volume basis using a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium. In Example 5, TZ-3Y (Y2O3 content: 3 mol%):TZ-6Y (Y2O3 content: 6 mol%) were mixed in a ratio of 18.7:81.3, and the ratio of each component was adjusted to the blending ratio shown in Table 1.

[0118] [Preparation of molded body] For each of the Examples and Comparative Examples, pellet-shaped compacts and block-shaped compacts were prepared as follows so as to obtain sintered body samples for evaluating translucency and strength and for evaluating processability. For the pellet-shaped compact, a cylindrical mold having a diameter of 19 mm was used, and the raw material composition was placed in the mold so that the thickness of the zirconia composite sintered body after sintering would be 1.2 mm. Next, the raw material composition was press-molded at a surface pressure of 200 MPa using a uniaxial press molding machine to produce a pellet-shaped compact.

[0119] For the block-shaped compact, the raw material composition was placed in a mold having an inner dimension of 19 mm×18 mm so that the height of the zirconia composite sintered body after sintering would be 14.5 mm. Next, the raw material composition was press-molded at a surface pressure of 200 MPa using a uniaxial press molding machine to produce a block-shaped compact.

[0120] [Preparation of primary sintered body] The pellet-shaped and block-shaped compacts obtained were subjected to a sintering furnace "Noritake Katana (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd., and were subjected to sintering in the atmosphere at the maximum sintering temperature shown in Tables 1 to 3 for 2 hours to obtain pellet-shaped and block-shaped zirconia composite sintered body (primary sintered body) samples.

[0121] [Preparation of HIP-treated sintered body] The pellet-shaped and block-shaped zirconia composite sintered bodies obtained (primary sintered bodies) were subjected to a HIP apparatus "O2-Dr.HIP" manufactured by Kobe Steel, Ltd., at 150 MPa and the HIP temperatures shown in Tables 1 to 3 for 2 hours to obtain pellet-shaped and block-shaped zirconia composite sintered bodies (HIP-treated sintered bodies) samples.

[0122] [Preparation of zirconia composite sintered body (sintered body after tempering treatment)] The obtained pellet-shaped and block-shaped zirconia composite sintered bodies (HIP-treated sintered bodies) were subjected to a firing furnace "Noritake Katana (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd. at 700°C for 60 hours to obtain pellet-shaped and block-shaped zirconia composite sintered body samples (sintered bodies after tempering treatment). The pellet-shaped samples had a diameter of 15 mm and a thickness of 1.2 mm, while the block-shaped samples had a width of 15.7 mm, a length of 16.5 mm, and a height of 14.5 mm.

[0123] The content of each component of the sintered body in Tables 1 to 3 is a value calculated from the charged amount of the raw material. The content (mol %) of the Group I elements in Tables 1 to 3 is the external addition rate relative to a total of 100 mol % of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. The content (mol%) of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 in Tables 1 to 3 is the content of each component in a total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. Only ZrO2 and HfO2 are shown as the total content of ZrO2 and HfO2. The content (mass %) of TiO2 in Tables 1 to 3 is the external addition rate relative to the total of 100 mass % of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. In Tables 1 to 3, A / B represents the ratio of A to B when the content of Y2O3 is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %.

[0124] [Translucency evaluation of zirconia composite sintered body] The samples (diameter about 15 mm × thickness 1.2 mm) of the pellet-shaped zirconia composite sintered body (sintered body after tempering treatment) of each Example and Comparative Example were used as they were, and the translucency was evaluated by the following method (n = 3). As a measuring device, Olympus Corporation's dental color measuring device "Crystal Eye" (7 band LED light source) was used, and first, the background (underlay) of the sample was made white (the opposite side of the measuring device with respect to the sample was made white) and the L* value of the L*a*b* color system (JIS Z 8781-4: 2013 Colorimetry-Part 4: CIE 1976 L*a*b* color space) was measured, which was defined as the first L* value. Next, for the same sample for which the first L* value was measured, the background (underlay) of the sample was made black (the opposite side of the measuring device with respect to the sample was made black) and the L* value of the L*a*b* color system was measured, which was defined as the second L* value. In the present invention, the difference between the first L* value and the second L* value (the value obtained by subtracting the second L* value from the first L* value) is regarded as the light transmittance, and is expressed as ΔL*. A high ΔL* value indicates high light transmittance, and a low ΔL* value indicates low light transmittance. For the black and white background (underlay) in the chromaticity measurement, a hiding power test paper used for measurements related to paints described in JIS K 5600-4-1:1999 can be used. The average ΔL* values ​​of each sample are shown as results in Tables 1 to 3. A ΔL* of 10 or more was considered to be acceptable.

[0125] [Strength evaluation of zirconia composite sintered body] The biaxial bending strength of the pellet-shaped zirconia composite sintered body (sintered body after tempering) samples of each Example and Comparative Example was measured as is using a universal testing machine "AGS-X" (manufactured by Shimadzu Corporation) at a crosshead speed of 1.0 mm / min in accordance with ISO6872:2015 (n=5). The average values ​​are shown in Tables 1 to 3 as the measurement results. A strength of 350 MPa or more was considered to be acceptable.

[0126] [Method for measuring average crystal grain size in sintered body] For each of the pellet-shaped zirconia composite sintered bodies (sintered bodies after tempering treatment) of the Examples and Comparative Examples, images of the surfaces were taken with a scanning electron microscope (product name "VE-9800", manufactured by Keyence Corporation). After the grain boundaries of each crystal grain were noted on the obtained images, the average crystal grain size was calculated by image analysis. The average crystal grain size was measured using image analysis software (product name "Image-Pro Plus", manufactured by Hakuto Co., Ltd.), the captured SEM image was binarized, the brightness range was adjusted so that the grain boundaries were clear, and the particles were recognized from the field of view (area). The crystal grain size obtained with Image-Pro Plus was the average of the lengths of the line segments connecting the outlines passing through the center of gravity determined from the outlines of the crystal grains, measured at intervals of two degrees from the center of gravity, and the average value of the crystal grain size of all the particles not overlapping the edge of the image in the SEM photograph images (three fields of view) of each Example and Comparative Example was taken as the average crystal grain size (number basis) in the sintered body. "Particles not on the image edge" refers to particles excluding those whose outlines do not fit within the screen of the SEM photograph (particles whose outlines end at the top, bottom, left, and right boundaries). The crystal grain size of all particles not on the image edge was determined by selecting the option to exclude all particles on the boundary lines in Image-Pro Plus.

[0127] The average crystal grain size of the crystal grains in the zirconia composite sintered body of Example 1 was 2.7 μm, and the average crystal grain size of the crystal grains in the zirconia composite sintered body of Example 14 was 2.2 μm.

[0128] [Evaluation of workability of zirconia composite sintered body] Thirty samples of block-shaped zirconia composite sintered bodies (sintered bodies after tempering) of each Example and Comparative Example were prepared with a metal jig attached to a surface of about 15.7 mm wide x 14.5 mm high, and processed into a general anterior tooth crown shape using a CEREC system "MC-XL" (manufactured by Dentsply Sirona). The processing program used the software "inLab (registered trademark) CAM version 20.0.1.203841", and the following settings were selected: Manufacturer: IVOCLAR VIVADENT, Material name: IPS e.max CAD, Production Method: Grinding, Block size: C16, and the processing tools used were Step Bur 12 and Cylinder Pointed Bur 12S.

[0129] [Processing time] The processing times shown in Tables 1 to 3 are the times required to complete processing of the first sample using new processing tools under the conditions described in [Evaluation of processability of zirconia composite sintered body] above. In addition, if an error occurred due to the load during processing, etc., and the CEREC system "MC-XL" stopped midway through processing, a new processing tool was attached and processing was restarted. This operation was repeated until processing of one sample was completed, and the time required was recorded as the processing time.

[0130] [Number of pieces] The number of processed pieces shown in Tables 1 and 3 is the number of samples that could be processed into the shape of a front tooth crown without changing the processing tool once, using a new set of processing tools and starting processing of the samples under the conditions described in the above [Evaluation of the processability of zirconia composite sintered body]. The maximum number of samples used for the test was 30, and if processing of up to 30 samples could be completed with one processing tool, additional processing tests were not performed, and the number was uniformly set to "30 or more." Furthermore, if an error occurs due to the load during machining or the like before the first sample is processed and the MC-XL stops midway, a new machining tool is attached and machining is restarted. This operation is repeated until one sample is processed, and the reciprocal of the number of machining tools used is taken as the number of samples processed. For example, "0.2 pieces" in Comparative Example 1 in Table 3 means that five machining tools were used to obtain a sample machined into the crown shape of one front tooth. The results are shown in Tables 1 to 3 below.

[0131] [Table 1]

[0132] [Table 2]

[0133] [Table 3]

[0134] From the above results, it was confirmed that the zirconia composite sintered body of the present invention has strength and translucency suitable for dental use, and also has excellent machinability. Moreover, in Examples 1 to 34, wear of the processing tool could be suppressed, and the number of dental prostheses that could be continuously processed with one processing tool could be increased compared to the conventional technology. On the other hand, in Comparative Examples 1 and 2, which did not contain a Group I element, the reduction in processing time was not sufficient. Comparative Examples 3 and 8, which did not contain TiO2, did not have sufficient strength. In Comparative Example 4, in which the content of Nb2O5 was too high, and Comparative Example 7, in which the content of Y2O3 was too low, the samples were chipped or peeled off, and the physical properties could not be measured. In Comparative Example 5, in which the content of Nb2O5 was too low, the shortening of the processing time was not sufficient. In Comparative Example 6, in which the content of Y2O3 was too high, the shortening of the processing time was not sufficient.

[0135] Furthermore, Patent Document 1 indicates that increasing the amount of TiO2 added reduces the strength in proportion to the amount added (FIG. 7). However, it has been confirmed that when the zirconia composite sintered body of the present invention contains Nb2O5 and / or Ta2O5 as components, by further containing a Group I element and TiO2, these components act together to improve the translucency and strength of the zirconia composite sintered body, thereby obtaining a zirconia composite sintered body that combines excellent machinability, translucency, and strength. [Industrial Applicability]

[0136] The zirconia composite sintered body of the present invention has suitable strength and translucency, and is excellent in machinability, and is particularly useful as a dental material for dental prostheses and the like for dental treatment applications.

Claims

1. ZrO 2 and HfO 2 a stabilizer capable of suppressing the phase transition of zirconia; and Nb 2 O 5 And / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In a total of 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, Further, Group I elements and TiO 2 The zirconia composite sintered body comprises:

2. TiO 2 The content of ZrO 2 and HfO 2 and the stabilizer, and Nb 2 O 5 and Ta 2 O 5 The zirconia composite sintered body according to claim 1, wherein the zirconia composite sintered body has a content of more than 0 mass% and 5.0 mass% or less with respect to a total of 100 mass%.

3. The content of the Group I element is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 The zirconia composite sintered body according to claim 1 or 2, wherein the content of each of the zirconia compounds is more than 0 mol% and 3 mol% or less with respect to a total of 100 mol%.

4. The zirconia composite sintered body according to any one of claims 1 to 3, wherein the Group I element includes at least one element selected from the group consisting of Li, Na, and K.

5. The content of the stabilizer is expressed as Amol%, and Nb 2 O 5 and Ta 2 O 5 When the total content is B mol%, The zirconia composite sintered body according to any one of claims 1 to 4, wherein A / B is 0.9 or more and 3 or less.

6. The stabilizer is Y 2 O 3 and / or CeO 2 The zirconia composite sintered body according to any one of claims 1 to 5, comprising:

7. TiO 2 The zirconia composite sintered body according to any one of claims 1 to 6, wherein the content of is 0.6 mass% or more and 4.3 mass% or less.

8. The zirconia composite sintered body according to any one of claims 1 to 7, having a biaxial bending strength measured in accordance with ISO 6872: 2015 of 350 MPa or more.

9. The zirconia composite sintered body according to any one of claims 1 to 8, wherein the average crystal grain size of the zirconia composite sintered body is 0.5 to 5.0 μm.

10. ZrO 2 and HfO 2 a stabilizer capable of suppressing the phase transition of zirconia; and Nb 2 O 5 And / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In a total of 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, Furthermore, the raw material compounds of Group I elements and TiO 2 A step of producing a molded body using a raw material composition comprising: and sintering the compact. The method for producing the zirconia composite sintered body according to claim 1.

11. the source compound of the Group I element is a hydroxide and / or a salt of the Group I element, The method further includes a step of wet-mixing each of the raw materials of the raw material composition in a solvent containing water to obtain a raw material composition. The method for producing the zirconia composite sintered body according to claim 10.

12. In the raw material composition, the stabilizer is ZrO 2 and HfO 2 The method for producing a zirconia composite sintered body according to claim 10 or 11, further comprising a stabilizer that is not solid-dissolved in the zirconia composite sintered body.

13. In the step of sintering the molded body, sintering at 1300 to 1680°C; The process includes a step of HIP treatment at 1200°C or higher. The method for producing the zirconia composite sintered body according to any one of claims 10 to 12.

14. After the HIP treatment, a heat treatment step is performed at 1400° C. or less in air or in an oxygen-rich atmosphere. The method for producing the zirconia composite sintered body according to claim 13.

Citation Information

Patent Citations

  • Machinable zirconia and method for producing the same

    JP2015127294A

  • Production method for workable zirconia composite sintered body, raw material composition for workable zirconia composite sintered body, and workable zirconia composite calcined body

    WO2021132644A1